Toxicity and Carcinogenicity of Dichlorodiphenyltrichloroethane (DDT) - Harada, Takanori (Korean Society of Toxicology, 2016)
Dichlorodiphenyltrichloroethane (DDT) is still used in certain areas of tropics and subtropics to control malaria and other insect-transmitted diseases. DDT and its metabolites have been extensively studied for their toxicity and carcinogenicity in animals and humans and shown to have an endocrine disrupting potential affecting reproductive system although the effects may vary among animal species in correlation with exposure levels. Epidemiologic studies revealed either positive or negative associations between exposure to DDT and tumor development, but there has been no clear evidence that DDT causes cancer in humans. In experimental animals, tumor induction by DDT has been shown in the liver, lung, and adrenals. The mechanisms of hepatic tumor development by DDT have been studied in rats and mice. DDT is known as a non-genotoxic hepatocarcinogen and has been shown to induce microsomal enzymes through activation of constitutive androstane receptor (CAR) and to inhibit gap junctional intercellular communication (GJIC) in the rodent liver. The results from our previously conducted 4-week and 2-year feeding studies of p,p′-DDT in F344 rats indicate that DDT may induce hepatocellular eosinophilic foci as a result of oxidative DNA damage and leads them to hepatic neoplasia in combination with its mitogenic activity and inhibitory effect on GJIC. Oxidative stress could be a key factor in hepatocarcinogenesis by DDT.